2017
DOI: 10.1139/facets-2016-0074
|View full text |Cite
|
Sign up to set email alerts
|

First North American occurrences ofQiupalong(Theropoda: Ornithomimidae) and the palaeobiogeography of derived ornithomimids

Abstract: Ornithomimid material from the Belly River Group (Campanian) of Alberta, Canada is described as sharing characters with Qiupalong henanensis from the Qiupa Formation of Henan Province, China. Derived characters and character combinations of the pubis and astragalocalcaneum were previously used to diagnose Q. henanensis and support the referral of this material to Qiupalong sp., representing the first known occurrences of Qiupalong outside of China. Qiupalong is the sixth ornithomimid taxon to be reported from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…4), having a weak posteromedial ridge at the distal end and equally projecting distal malleoli. McFeeters, Ryan, Schröder-Adams, and Currie (2017) attributed to Qiupalong sp. several fragmentary ornithomimid specimens from the Campanian Dinosaur Park Formation of Alberta, Canada, and concluded that it is the first ornithomimid genus with a transcontinental distribution.…”
Section: Discussionmentioning
confidence: 99%
“…4), having a weak posteromedial ridge at the distal end and equally projecting distal malleoli. McFeeters, Ryan, Schröder-Adams, and Currie (2017) attributed to Qiupalong sp. several fragmentary ornithomimid specimens from the Campanian Dinosaur Park Formation of Alberta, Canada, and concluded that it is the first ornithomimid genus with a transcontinental distribution.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Jasinski et al (2020), there may still be some vicariance between biogeographical regions. There is a clear connection between many of the dinosaurs (e.g., ankylosaurids, hadrosaurids, pachycephalosaurids, ornithomimids, tyrannosaurids) of Asia and North America during the Late Cretaceous (e.g., Arbour et al, 2014; Brusatte and Carr, 2016; Dalman et al, 2017; Jasinski & Sullivan, 2011, 2016; Lucas et al, 2016; McFeeters et al, 2017; Prieto‐Márquez, 2010; Sullivan, 1999, Sullivan & Lucas, 2003, Sullivan & Lucas, 2006) and how these came about, including possibilities for migration patterns, vicariance, and/or convergence, still need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a calcaneum that is deeply incised and an ascending process inset from the lateral surface of the astragalocalcaneum both argue for a non-oviraptorosaur identity of TMP 1993.036.0631 and TMP 1995.074.0049. Instead, these elements are identical to those described by McFeeters et al (2017), and should therefore be regarded as ornithomimids.…”
Section: Caenagnathus Collinsimentioning
confidence: 92%